2012
DOI: 10.3109/13625187.2012.670889
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive practices of women requesting induced abortion in Spain: A cross-sectional multicentre study

Abstract: Despite the use of effective contraceptive methods, the majority of women requesting induced abortion in Spain became pregnant during the use of these methods. These data reflect a lack of compliance. More education programmes are needed to improve compliance rates. The long-acting reversible contraceptive methods could constitute an appropriate approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
5
14
0
7
Order By: Relevance
“…Women did not know how to deal with missing a pill and had very little awareness of forms of contraception and emergency contraception [ 21 , 22 ]. According to Serrano et al [ 23 ] failure of contraceptive use was reported by 77 % of those using condoms and by 84 % of those using hormonal contraception. In fact, a rise in contraceptive use must be combined to effectiveness of use to obtain a decline in induced abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Women did not know how to deal with missing a pill and had very little awareness of forms of contraception and emergency contraception [ 21 , 22 ]. According to Serrano et al [ 23 ] failure of contraceptive use was reported by 77 % of those using condoms and by 84 % of those using hormonal contraception. In fact, a rise in contraceptive use must be combined to effectiveness of use to obtain a decline in induced abortion.…”
Section: Discussionmentioning
confidence: 99%
“…La mayoría de los abortos se realizan en mujeres que refieren haberse embarazado a pesar de utilizar el preservativo 66,67 . Según la Sociedad Española de Contracepción, la efectividad del preservativo es limitada.…”
Section: Discussionunclassified
“…PREKIDA TRUDNOĆE U odnosu na upotrebu kontracepcije, artificijelni prekid trudnoće je direktna posledica neupotrebljavanja kontraceptiva, jer se većina registrovanih legalnih prekida trudnoće odnosi na trudnoće nastale usled neprimenjivanja kontraceptivnih metoda, dok znatno manji broj otpada na trudnoće do kojih je došlo tokom primene kontraceptiva [37,38]. Bongaarts i Westoff, ispitujući ulogu povećanja prevalence upotrebe kontraceptiva i njihove efikasnosti u smanjenju stope artificijelnih prekida trudnoće, analizirali su model koji povezuje stopu artificijelnih prekida trudnoće sa direktnim determinantama koje uključuju reproduktivne preference para, prevalencu i efikasnost praktikovanja kontracepcije i verovatnoće podvrgavanju artificijelnom prekidu neplanirane trudnoće, u cilju izbegavanja rađanja neplaniranog deteta, u slučaju neuspeha kontraceptivnog metoda ili njegovog nekorišćenja.…”
Section: Odnos Kontracepcije I Artificijelnogunclassified